1970
DOI: 10.13057/biodiv/d050201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and organic substrate on growth and activities of ammonia-oxidizing bacteria

Abstract: The physiological character, especially the effect of pH and organic substrate on the growth and activity of some ammoniaoxidizing bacteria was carried out. The results show that eight out of twenty isolates have ability to reduce ammonium, two of them i.e. isolate AOB1 and AOB2 could reduce more than 90% of ammonium. The growth and activity to reduce ammonium to nitrite was attained optimum at pH 7-8. From the result also indicated that the growth and activity of both isolate AOB1 and AOB2 were higher on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
1
Order By: Relevance
“…However, the present study showed that biochar suppressed amoA-AOB and amoA-AOA gene abundance. The explanation was that biochar addition decreased the frequency of functional microorganisms by increasing the diversity of AOB and AOA, and increased soil pH (Table 1), which exceeded the optimum value for amoA growth and activity [50].…”
Section: Biochar Addition Shifted the Community Structures Of Aob And...mentioning
confidence: 99%
“…However, the present study showed that biochar suppressed amoA-AOB and amoA-AOA gene abundance. The explanation was that biochar addition decreased the frequency of functional microorganisms by increasing the diversity of AOB and AOA, and increased soil pH (Table 1), which exceeded the optimum value for amoA growth and activity [50].…”
Section: Biochar Addition Shifted the Community Structures Of Aob And...mentioning
confidence: 99%
“…Soil media was prepared by enriching the sieved soil material with a nitrification medium to stimulate nitrification activity and the growth nitrifier community. A liter of nitrification medium contained 0, 200, or 500 mg (NH4)2SO4; 725 mg KH2PO4; 1136 mg Na2HPO4; 50 mg MgSO4•7H2O; 20 mg CaCl2•2H2O; 1 mg Fe.EDTA; and 1 mL trace elements (Agustiyani et al 2004). The trace elements were made by dissolving 10 mg Na2MoO4•2H2O, 20 mg MnCl2•4H2O, 10 mg ZnSO4•7H2O, 0.2 mg CoCl2•6H2O, and 2 mg CuSO4•5H2O in 1000 mL aquabides (Agustiyani et al 2004).…”
Section: Preparation Of Soil Media and Nitrification Mediummentioning
confidence: 99%
“…A liter of nitrification medium contained 0, 200, or 500 mg (NH4)2SO4; 725 mg KH2PO4; 1136 mg Na2HPO4; 50 mg MgSO4•7H2O; 20 mg CaCl2•2H2O; 1 mg Fe.EDTA; and 1 mL trace elements (Agustiyani et al 2004). The trace elements were made by dissolving 10 mg Na2MoO4•2H2O, 20 mg MnCl2•4H2O, 10 mg ZnSO4•7H2O, 0.2 mg CoCl2•6H2O, and 2 mg CuSO4•5H2O in 1000 mL aquabides (Agustiyani et al 2004). All of the nitrification medium ingredients were dissolved in 1000 mL of distilled water and were sterilized at 121°C for 20 minutes.…”
Section: Preparation Of Soil Media and Nitrification Mediummentioning
confidence: 99%
“…Therefor Agrobacterium sp I37 added to the soil increased total microbial colonies in the soil. The more total microbial colonies in the soil, the greater the likelihood of interaction between microorganisms and root exudates, thereby enhancing the ability of plants to absorb heavy metals (Gadd, 2010;Agustiyani et al, 2004). The use of compost and inorganic fertilizers can supply C-organic in the soil thereby increasing the population of microorganisms (Zhang et al, 2015).…”
Section: Total Microbial Coloniesmentioning
confidence: 99%